From creation to disintegration of Yugoslavia - Haselhorst Urize, Tattila (Seven Editora, 2023)
Yugoslavia has a unique history in the 20th century. This article proposes to show the history of this country composed of six republics – Serbia, Montenegro, Croatia, Bosnia-Herzegovina, Slovenia and Macedonia. It should be shown how internal rivalries combined with external factors such as the world system contributed to its disintegration. Yugoslavia’s relationship with hegemonic powers such as the United States and the USSR and with large financial institutions such as the IMF and the World Bank will also be analyzed. The place occupied by this state in the world system is essential to explain its collapse. DOI: 10.56238/pacfdnsv1-025